Edible film instant noodle / Adibah Zurkafli ... [et al.] - Zurkafli, Adibah; Mohamad Suhaili, Ain Nur Aisyah; Munif Zarirruddin Zikri, Mawaddah; Junaidi, Nur Farisha Jane; Shahrizan, Nurfatini Iman; Che Aslan, Nurul Ain Nabilah (2023)
Slurp! Enterprise, a food processing company in Malaysia, is committed to producing products that align with modern and eco-friendly values. This company's development focuses on promoting convenience and incorporating biodegradable packaging. To achieve this, our team researched and developed instant noodles using edible packaging film, specifically seaweed. As a result, the company has introduced an edible film instant noodle that prioritises biodegradability and convenience while advancing food packaging technology. Ideal for individuals with busy lifestyles, this new option offers a delicious and easy-to-prepare meal that can be made by simply adding hot water. The target market for this edible film instant noodle is young adults between 18 and 30, including students, workers, and travellers. Slurp! Enterprise has identified this group as particularly likely to purchase the product by segmenting them based on common characteristics such as demographics, behaviour, and psychographics. Our team did market research and analysis by performing concept and market testing by distributing online questionnaires consisting of 5 questions and distributing complimentary samples to potential customers. Slurp! Enterprise introduced the new edible film instant noodle with several advantages over other instant noodles on the market, such as being more environmentally friendly with its biodegradable packaging, more convenient to prepare as customers only need to add hot water, and it promises a delicious taste. Additionally, it is suitable for the current lifestyle that demands something quick, delicious, and convenient to prepare. The use of edible film packaging technology is a new and innovative approach in the instant noodle market, giving Slurp! Enterprise a competitive edge over other competitors.